Empirical analysis on the real effects of inflation and exchange rate uncertainty: The case of Colombia (2020)
This paper re-examines the effects of inflation and exchange rate uncertainty on real economic activity. The existent literatura has treated both issues as separate subject matters. It has emphasized either the issue of inflation uncertainty or exchange rate uncertainty on economic growth or on different measures of economic activity. This paper attempts dealing with both issues by analyzing the magnitudes and direction of the effect of both: inflation and exchange rate uncertainty on real economic activity. By introducing dummy variables, we control for monetary policy change (the change to inflation targeting and flexible exchange rate). By using a generalized autoregressive conditional variance (GARCH) model of inflation and exchange rates, the conditional variances of the model’s forecast errors were extracted as measures of uncertainty. The results suggest that higher levels of inflation Granger cause more uncertainty and viceversa for the Colombian economy. Also, only inflation uncertainty matters for output by exerting a negative influence